P963Recurrence of atrial fibrillation after cryoballoon pulmonary vein isolation in overweight and obese patients - does weight matter?. (18th June 2020) - Weinmann, K; Gillmeister, S; Aktolga, D; Bothner, C; Rattka, M; Rottbauer, W; Dahme, T; Pott, A
Abstract: Funding Acknowledgements: Karolina Weinmann was supported by the Hertha-Nathorff fellowship from Ulm University Background - Obesity is a known risk factor for the incidence and persistence of atrial fibrillation. Many interventional studies proved losing weight correlates with less atrial fibrillation (AF) burden. Purpose – We investigated the influence of overweight and obesity on baseline characteristics, procedural values and outcome after cryoballoon pulmonary vein isolation (cryoballoon PVI). Methods – We investigated 575 patients undergoing cryoballoon PVI at our Medical Center. 142 patients were classified as normal with a body mass index (BMI) of 18.5 – 24.9 kg/m², 239 patients presented overweight with a BMI of 25.0 – 29.9 kg/m² and 194 patients were obese with a BMI over 30.0. We compared the baseline characteristics, the procedural and outcome data of these patients. Results – Comparing baseline characteristics of overweight and obese patients to normal weight patients, obese show the highest portion in hypertension (obese vs. normal: 86.1% vs. 68.3%, p < 0.001), diabetes (26.8% vs. 14.8%, p < 0.05), OSAS (17.0% vs. 2.1%, p < 0.001) and left atrial (LA) diameter (44.6 ± 10.8mm vs. 41.3 ± 12.7mm, p < 0.05). Comparison of procedure duration, fluoroscopy time and area dose product (Gy*cm²), only the area dose product shows a significantly higher value in the overweight and obese patients (p < 0.001). Moreover, comparing the duration of ablation, time to isolation per pulmonary vein between the three groups, the overweight and obese patients show a significantly longer duration of ablation at the RSPV and the time to isolation is significantly higher at the LSPV. Mean follow-up period in our cohort is 517.3 ± 461.3 days (1.4 ± 1.3 years). Kaplan-Meier estimation shows no significant difference between freedom from AT/AF recurrence comparing normal weight, overweight and obese patients (Log-rank p = 0.6). After one year follow-up, 70% of normal weight patients show freedom from atrial arrhythmia recurrence and 69% of overweight patients.  Obese patients have a fraction of 75% of freedom from AT/AF recurrence after one year. Comparing the two years follow-up values 56% of the normal BMI patients, 54% of the overweight patients and 62% of obese patients are free from arrhythmia recurrence. Conclusion – Cryoballoon PVI procedure in obese and overweight patients is a feasible treatment, however the radiation exposure is higher compared to normal weight. Evaluating outcomes, no difference in recurrence of AF was detected between normal, overweight and obese patients after cryoballoon PVI.